Post-synthetic oriented attachment of CsPbBr3 perovskite nanocrystal building blocks: from first principle calculation to experimental demonstration of size and dimensionality (0D/1D/2D). Issue 6 (8th April 2020) - Jeon, Sanghyun; Jung, Myung-Chul; Ahn, Junhyuk; Woo, Ho Kun; Bang, Junsung; Kim, Donggyu; Lee, Sang Yeop; Woo, Ho Young; Jeon, Jongchul; Han, Myung Joon; Paik, Taejong; Oh, Soong Ju
Abstract : Immiscible solvent treatment induced oriented attachment of perovskite nanocrystal, resulting in change of size and dimensionality (0D/1D/2D). Abstract : Post-synthesis engineering methods that employ oriented attachment to precisely control the size and dimensionality (0D/1D/2D) of as-synthesized CsPbBr3 nanocrystals (NCs) are demonstrated. We investigated the chemical effects of the properties of polar solvents, including their immiscibility, polarity, and boiling point, on the surfaces of NCs, as well as their effect on the structural and optical properties of NCs. Appropriate exploitation of the solvent properties made it possible to use a polar solvent to mildly affect the NCs indirectly such that they discarded their ligands and became attached to proximal NCs without being destroyed. Based on our observations, we developed a method whereby a solution of the NCs in a non-polar solvent is mixed with a polar solvent to form an immiscible phase to induce epitaxial growth of CsPbBr3 NCs. The method enables the size of NCs to be easily regulated from 5 to 50 nm by controlling the engineering time. Taking advantage of the minimal effect of a mild solvent, we also developed a self-assembly method that operates at the liquid–air interface to systematically control the dimensionality. At this interface, the NCs self-assemble in the horizontal direction and grow into micron-sized, single-crystalline, defect-free nanowires (1D) and nanoplates (2D) via oriented attachment. Finally, we discuss the origin of the non-destructive oriented attachment phenomenon and the surface chemistry of a perovskite NC using density functional theory (DFT) simulations and a proposed model system.